ANALISIS TEKNIK PELAKSANAAN SAMBUNGAN TULANGAN KOLOM PEDESTAL RANGKA ATAP MENGGUNAKAN METODE CHEMICAL ANCHOR PADA PROYEK GEDUNG AUDITORIUM - Nabila Fiqi; Edo Barlian; Daniel Anderson Munthe; Nazwa Qaila; Izmi Khairani; M. Wisnu Widjaya (Universitas Muhammadiyah Metro, 2026)
A pedestal column is a relatively short vertical structural element that functions to transfer loads from the superstructure to the foundation. In the construction project of the Progressive Auditorium Building at Muhammadiyah University of North Sumatra (UMSU), the reinforcement connection of the roof-frame pedestal columns could not be installed simultaneously with the foundation casting due to design modifications and installation errors encountered on site. Consequently, the chemical anchor method was adopted as a technical solution. This study aims to analyze the implementation technique of the reinforcement connection, including its compliance with applicable standards and the challenges encountered during field execution. A qualitative descriptive approach was employed, with data collected through direct observation, documentation, interviews with technical personnel, and literature review. The chemical anchoring product used was Hilti HIT-RE 500 V3, with D22 reinforcing bars, a drilling diameter of 25 mm, and an embedment depth of 200 mm. Data were analyzed descriptively by comparing field implementation practices with the requirements of ETAG 001 Part 5 (Bonded Anchors) and SNI 2847:2019 concerning Structural Concrete Requirements for Buildings. The evaluation of six implementation stages indicated that five stages—drilling point determination, hole cleaning, resin injection, reinforcement installation, and a 24-hour curing process—were carried out in accordance with the prescribed standards. One stage requiring improvement was the drilling process, where the drill bit encountered existing reinforcing bars embedded in the concrete at several locations. As a result, drilling had to be repeated at adjusted positions while maintaining the required reinforcement spacing and compliance with the construction drawings. The primary cause of this issue was the inability to identify the exact location of the existing reinforcement during the drilling point marking stage. Overall, the application of the chemical anchor method in this project produced a bond between the new reinforcement and the existing concrete that satisfied the applicable standards and construction requirements. Therefore, this method can serve as a technical reference for similar projects involving phased construction of educational institutional buildings.